The Youth, The Sciences Students, and Religious Radicalism - Yusar Yusar (Al-Ulum, 2016)
This article is an endeavor to describe the tendency of religious radicalism amongst student of science at senior high schools and the students of several universities such as the faculty of medicine, pharmacy, and agriculture.. In many cases students or young people are the main target of the religious radicalism agents. The youth then receive the transmission of the religious radicalism and regenerate those values. In fact, the students of sciences, as individual with science education are more likely become member of religious radicalism group than other students such as humanities or social science. Why? This article portrays the causality of one’s joined the religious radicalism group by the micro sociological approaches divided into two main factors such the individual states of minds of their world views and the student’s relative deprivation.